Aplikasi Kompos dan Arang Aktif Sebagai Bahan Amelioran di Tanah Berpasir Terhadap Pertumbuhan Tanaman Caisim (Brassica juncea L.) - Priyadi Priyadi; Jamaludin Jamaludin; Windu Mangiring (Jurnal Penelitian Pertanian Terapan, 2018)
One of the efforts in sandy soil utilization is to add ameliorant material. The addition of ameliorant material can use compost that plays an important role in improving the physical, chemical and biological properties of the soil. The purpose of this study was to determine the effect of compost and activated charcoal as ameliorant material on sandy soil to the growth of mustard plant (Bressica juncea L). The study was conducted at Greenhouse of STIPER Dharma Wacana Metro, while soil analysis was conducted in Taman Bogo Soil Research Laboratory. The results showed that the use of ameliorant material in the form of activated charcoal and compost can improve the sandy soil properties as indicated by the increase of pH, moisture content, C-organic, and N-total. The highest effect of growth was shown in the treatment of PK that is 9.86 gram. While, the highest growth of plant roots is shown in 1.07 gram of PKA treatment. In general, the use of ameliorants in this study has a good effect in the change of sandy soil properties and growth in mustard plants.